S.R. Ranganathan : Classic And Contemporary Views On His Life And Work - Satija, M.P; Avila, Daniel. Martinez; Almeida, Patricia. De; National Library (India) (Ne Delhi : Ess Ess Publication, 2024)
Contains articles highlighting the different facets of Prof. Ranganathan's contribution in the field of library development.
Includes bibliographical references.
Keywords: .; Library science -- India -- History -- 20th century; Librarians -- India -- Biography